An extended GEDM method with heterogeneous reference points of decision makers and a new hesitant fuzzy distance formula. (August 2020) - Wang, Zhiying; Nie, Huifang; Zhao, Hongli
Highlights: A model is given to describe heterogeneous reference points caused by DMs' emotions. A new hesitant fuzzy distance formula is proposed. An optimal model is established to obtain the weights of DMs. Abstract: Group emergency decision-making (GEDM) method based on cumulative prospect theory has been widely concerned by scholars, but few of them have paid attention to the heterogeneous references points (HRPs) of decision-makers (DMs) caused by their emotions. In addition, hesitant fuzzy sets are often used to cope with incomplete information in GEDM, but where the exiting distance formulas used cannot keep fuzziness of the original decision information and retain the hesitancy of DMs. Therefore, an extended GEDM method is proposed. First, the GEDM problem is described and the relevant decision information is represented in the form of hesitant fuzzy numbers. Second, a quantitative model is given to describe the HRPs of DMs caused by their emotions and a new hesitant fuzzy distance formula is proposed. Then, the scenario values of alternatives and the decision weights of scenarios are calculated, and the comprehensive values of alternatives are calculated. Further, an optimal model is established to obtain weights of DMs, and based on which the weighted values of alternatives are calculated to obtain the ranking of alternatives. Finally, a case study and the comparison with other methods are carried out to demonstrate the effectiveness of the proposed method.